Crystallization and phase separation in thin film polymers - Jiang, L (2014)
Properties of polymers in thin films are distinct from those in the bulk due to the significant effects of free or substrate surfaces. The presence of a free surface allows an increased mobility of polymer chains in the near surface region, therefore, a lower glass transition temperature (Tg). With this lower surface Tg, a surface-specific crystallization phenomenon occurring at temperatures much lower than the bulk crystallization temperature (Tc) in polymers including PET, PEN and PVOH has previously been observed. However, whether or not this surface-specific crystallization is a phenomenon observable in all crystallizable polymers is still a question. Similarly, due to this greater mobility, phase separation may also be able to take place in the near-surface region of a polymer blend at a temperature much lower than the bulk phase separation temperature. Yet, no such investigation on polymer blends has been carried out. In addition, it is interesting to study the thin-film behaviours of a block copolymer that undergoes both phase separation and crystallization and compare these with corresponding bulk behaviour. In this thesis, the thin-film crystallization behaviour of polyamide 12 (PA12) in spin-cast films is presented together with some investigation of crystallization of polyamide 6 (PA6) and polystyrene. Polystyrene and poly(methyl methacrylate) (PS/PMMA) systems are used to illustrate the phase behaviours specific to the near-surface region. Finally, the microstructural evolution in high hard block content thermoplastic polyurethane (TPU) thin films on annealing has also been investigated. These TPUs have hard segments (HS) extended by 2 methyl 1,3 propanediol (2M13PD) or 1,5 pentanediol (15PD). With its flexible chains, PA12 crystallizes during spin coating forming as-spin-cast crystals with morphology that varies with solvent evaporation rate and film thickness. Despite the as spin-cast crystals, the free surface allows secondary surface crystallization of PA12 at an annealing temperature (Ta) roughly 20°C below the bulk Tc. The secondary surface crystals were indicated to exist in the most stable crystalline phase of PA12. Similar secondary surface crystallization has also been observed in the PA6 films but at a higher Ta due to the higher Tg of PA6. In addition, surface-specific crystals have been observed in PS (semicrystalline, likely due to some stereoregularity of composition), a polymer with bulky side groups. The PS surface crystals are, however, flat-on oriented showing the important effect of side groups on the morphology or growth shape of surface crystals. The discovery of these surface crystals supports the universality of surface specific crystallization. Using fast solvent quenching, it is possible to "freeze in" a structure containing both PS and PMMA in the near surface region. On annealing, surface-specific phase behaviours (observable as pits, undulations and aggregations) confined to the near-surface region take place first at temperatures around or just below the bulk polymer Tg, while bulk vertical phase separation and dewetting of PS to PMMA, forming holes, network structures and islands, occur at temperatures well above Tg. This surface specific phenomenon, being a result of the free surface, should be applicable to other phase separation systems with a free surface as well. An increase in the crystallinity of PS was found to promote the phase separation process, but the free surface effect is independent of the interplay between the crystallization and phase separation. Rather than having a two-phase morphology, as was previously observed in melt-quenched bulk samples, 2M13PD extended TPU spin-cast films showed a single-phase morphology as-spin-cast. However, the HS ordering, the formation of mesophase, the melting of HS ordered regions, and microphase mixing observed in thin films are consistent with the bulk results but with slightly different transition temperatures due to spatial confinement. With a more flexible chain extender, e.g. 15PD, the hard and soft phase separation is more limited. The thin film investigations have allowed a better understanding of the microstructural evolution in these high hard block content TPUs on annealing by imaging the morphology directly. A thin-film specific phenomenon: formation of large multilayer flat-on crystals, was also observed in these TPU thin films. These crystals are initially developed from preformed aggregations and are believed to be induced by the significant substrate effect in thin films and the free surface effect.